Home Production–A Forgotten Industry - Gronau, Reuben (The Review of Economics and Statistics, 1980)
Introduction R ECENT years have witnessed an awakened interest in the economic activity taking place outside the market, and in particular the activity taking place at home.This interest spurred by the new consumption theory of Becker and Lancaster and by the estimates of the Measure of Economic Welfare of Nordhaus and Tobin (1973) has taken two distinct forms: an increased number of studies on the economics of household behavior and a renewed effort to place a money value on the household home activity.However, while the major thrust of the first type of studies is in the field of microeconomics, the estimates of home production refer, in general, to the economy as a whole.These estimates, crude as they are, indicate that home production is far from being a negligible part of the economic activity.Even in an advanced economy such as the United States the value added generated by the home sector seems to account for over one third of the output produced at the market (Hawrylyshyn, 1976).In less advanced economies this fraction is presumably even higher.It seems, therefore, of interest to repeat the question in a microeconomic context and examine the role of home production at the household level, rather than in the aggregate.In contrast to past studies which have focused on the labor inputs going into home production (Sirageldin, 1969; Walker and Gauger, 1973), the emphasis in this paper is on the measurement of productivity and total home output.The questions I try to answer are: What are the factors